Malaysian Armed Forces Spiritual Strength Instrument - Mustaffa Al-Hafiz, Muhaidi; Jumahat, Tajulashikin; @ Jima'ain, Muhammad Talhah Ajmain; Syed Mansoor, Syarifah Bahiyah Rahayu (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
Spiritual strength plays a significant role within the armed forces as it enhances resilience and contributes to the effectiveness of military missions in maintaining national peace and security. Therefore, this study aims to validate a military psychological measurement instrument known as the Instrumen Kekuatan Spiritual Angkatan Tentera Malaysia (IKSAT-M), developed specifically to assess affective elements among members of the Malaysian Armed Forces (MAF). IKSAT-M was constructed based on the spiritual strength model proposed by Shantut (1989). This instrument measures six constructs of spiritual strength: Religious Adherence, Noble Character, Self-Confidence, Psychological Strength, Discipline, and Esprit de Corps, which were examined using factor analysis procedures. At the initial stage, the content of IKSAT-M was validated by five experts. Subsequently, an exploratory factor analysis (EFA) produced five factors and revealed that the constructs of Psychological Strength and Self-Confidence had merged. The development of IKSAT-M provides a new pathway for future research on the spiritual strength of MAF personnel.